One for the money [videorecording (DVD)] - Heigl, Katherine; O'Mara, Jason; Sunjata, Daniel, 1971-; Leguizamo, John; Shepherd, Sherri, 1967-; Reynolds, Debbie; Robinson, Julie Anne; Evanovich, Janet (Lions Gate Home Entertainment, 2012)
Stephanie Plum is a bright, attractive, confident woman whose entire life has just taken a sudden turn, in the totally wrong direction. Newly divorced and recently laid off, the only work she can scrape up is a dead-end job at her sleazy cousin's bail bond office. But when her first big assignment involves tracking down an on-the-lam ex-flame, this tough-as-nails lady bounty hunter will be redefining the meaning of hot pursuit.